Commissioning and evaluation of a radiochromic EBT3 film dosimetry system. Issue 1 (30th October 2018) - Isa Khan, Muhammad; Bilal Tahir, Muhammad; Rafique, Muhammad; Iqbal, Tahir; Zulfiqar, Sabiha; Zahoor, Aliza; Rehman, Jalil ur; Iqbal, Khalid; Chow, James
Abstract: Purpose: This work reports our study to commission a radiochromic film dosimetry system using the timely EBT3 film. We carried out dosimetric evaluations on different characteristics of photon beams (e.g., flatness, symmetry and penumbra) in radiation dose delivery. Materials and Methods: A Varian linear accelerator producing 6 and 15 MV photon beams with 120 multi-leaf collimator was used in this study. PTW ionisation chamber was used to measure the beam characteristics such as symmetry, flatness and penumbra and these measurements were used to commission the radiochormic EBT3 film dosimetry system. The results of irradiated films were analysed using the radiochromic film QA Pro software 2016. Results: The measured film doses were analysed at two different colour channels (green and red) using two scanning geometries (i.e., upper or lower side of film facing the scanner light source) at two dose levels (10 and 40 Gy). The difference between the ionisation chamber and film results was found insignificant and within the acceptable range as per the World Health Organisation standard. Conclusion: Results of the comparison between the ionisation chamber and film measurements show that our radiochormic EBT3 film dosimetry system is reliable and cost-effective in the output measurement of a linear accelerator. Our measurements confirm that our EBT3 film dosimetry agreed well with the ionisation chamber, and can be used as a re-validation tool for linear accelerator quality control.